On the Relationship Between Economic Freedom and Output Per Worker: The Case of Asia-Pacific Countries - Emara, Noha; Rebolledo, Loreto Reyes (International Journal of Economics and Financial Issues, 2019)
In this paper we study the effect of economic freedom on output per worker using a panel least square estimation methodology for a sample of 14 Asia-Pacific (APAC) and 18 OECD countries over the 1980-2014 period. This methodology allows us not only to study the relationship between the economic freedom and output per worker in APAC countries but also compare it with the empirical association between economic freedom and output per worker observed in OECD countries. The study also investigates the role of governance in affecting the impact of economic freedom on output per worker and its components. Our results indicate that 1) economic freedom has a positive and statistically significant impact on output per worker when we consider all countries in the sample and control for country-and time- fixed-effects. 2) A country’s economic freedom has a on its positive and statistically significant impact on its output per worker, but this effect higher for OECD countries than for APAC countries. 3) For APAC countries, a country’s size of government, legal system, and regulation has a positive and statistically significant impact on its output per worker. Keywords: APAC; Economic Freedom; Political Freedoms; Productivity; Corruption JEL Classifications: O16; O43; N20 DOI: https://doi.org/10.32479/ijefi.8252